1990
DOI: 10.1111/j.1365-2796.1990.tb01480.x
|View full text |Cite
|
Sign up to set email alerts
|

Vagal and sympathetic control of gastric and duodenal bicarbonate secretion

Abstract: Fandriks L, Jonson C (Department of Physiology, IJniversity of Goteborg. Goteborg. Sweden). Vagal and sympathetic control of gastric and duodenal bicarbonate secretion. journal of Internal Medicine 1990: 228, Suppl. 1 : 103-107.This report summarizes data concerning the extrinsic neural control of bicarbonate secretion by the gastric and duodenal mucosa. Parasympathetic vagal effects have been studied in experimental animals and in man by means of direct electrical vagal stimulation, sham-feeding procedures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These include vago-vagal reflexes (2,7,15,16,23), reflexes within the submucosal plexus of the enteric nervous system (12), C fiber efferent mechanisms (11,29), and inputs from the sympathetic nervous system (5,6,22). The interactions between these neural pathways have also been studied, and the findings suggest that secretomotor reflexes within the submucosal plexus are modified by vagal and sympathetic efferents that provide excitatory and inhibitory inputs, respectively, to submucosal neurons (6,22). These studies demonstrate that neural regulation of epithelial bicarbonate and mucin secretion from intestinal epithelium involves a complex interplay between extrinsic autonomic nerves and intrinsic secretomotor neurons in the submucosal plexus.…”
Section: Moore Beverley a David Kim And Stephen Vannermentioning
confidence: 99%
“…These include vago-vagal reflexes (2,7,15,16,23), reflexes within the submucosal plexus of the enteric nervous system (12), C fiber efferent mechanisms (11,29), and inputs from the sympathetic nervous system (5,6,22). The interactions between these neural pathways have also been studied, and the findings suggest that secretomotor reflexes within the submucosal plexus are modified by vagal and sympathetic efferents that provide excitatory and inhibitory inputs, respectively, to submucosal neurons (6,22). These studies demonstrate that neural regulation of epithelial bicarbonate and mucin secretion from intestinal epithelium involves a complex interplay between extrinsic autonomic nerves and intrinsic secretomotor neurons in the submucosal plexus.…”
Section: Moore Beverley a David Kim And Stephen Vannermentioning
confidence: 99%
“…The present results seem to be in consistent with the protective role of NO in the gastric mucosa. The HCO3 secretion in the stomach is known to increase in response to vagal excitation or agents that stimulate acid secretion (11,12). Barrachina et al (13) recently reported that L-NAME significantly reversed the antisecretory effect of endotoxin on distention-stimulated acid output and suggested the in volvement of NO in the regulation of acid secretion.…”
mentioning
confidence: 99%
“…[ 10 ] Vagal stimulation along with sympathetic irritation of gastric mucosa can be attributing factor for anxiety and emotional stress. [ 11 ] Data showed that aggravating factor in 17 (57%) patients was due to diet, 5 (17%) patients due to cold climate, 4 (13%) patients due to drug intake, while 3 (10%) patients by improper posture and 1 (3%) patient had occupation as aggravating factor. Intake of spicy food, Pitta Kaphavardhaka Ahara (food which aggravated Pitta and Kapha ) Vitiates Pitta , which causes Vidagdhaajirna .…”
Section: Discussionmentioning
confidence: 99%